Mortality-Related Factors and 1-Year Survival in Patients After Intracranial Stenting for Intracranial Arterial Critical Stenosis and Occlusion - Yusuf Inanc; Esra Polat; Mesut Karatas; Cengiz Sabanoglu; Kader Eliz Sahin; Ibrahim Halil Inanc (Medicina)
Background: Studies analyzing factors associated with mortality after intracranial stenting are limited. We aimed to investigate potential factors associated with 1-year mortality after urgent or elective intracranial stenting in those patients with intracranial atherosclerotic stenosis. Methods: Patients, who underwent urgent intracranial stenting of the target lesion either due to acute stroke unresponsive to mechanical thrombectomy, or who underwent elective stenting for symptomatic intracranial atherosclerotic stenosis were included in the study. The Modified Rankin Scale (mRS) score was evaluated on admission and grouped accordingly: ≤2 vs. >2. Restenosis and mortality rates in the 1-year follow-up were also analyzed. Results: A total of 60 patients were included in the study; the mean age was 60.2 (±10.8). The ratio of urgent/elective intracranial stenting was 7/53. Complete revascularization was achieved in all patients, but no periprocedural complications occurred. The rate of in-hospital mortality was 1/60, 1-year mortality due to any cause 4/60, and restenosis in a 1-year follow-up was 4/60. The age over 65 years, previous history of stroke, atrial fibrillation (AF), and rheumatic mitral valve disease were associated with mortality (p < 0.001, p = 0.002, p = 0.017, and p = 0.003, respectively). The median mRS score on admission was lower in the surviving patients at 1 year (p = 0.001). Conclusions: Intracranial stenting may provide long-term survival with low adverse event rates in elective and selected emergency cases. Advanced age, poor functional status, previous stroke, AF, and rheumatic mitral valve disease are associated with 1-year mortality.